HUBUNGAN PELATIHAN KADER DENGAN PENGETAHUAN KADER TENTANG PENEMUAN KASUS TUBERCULOSIS SECARA AKTIF - Putri, Sahda Alfreda; Viana, Nhemu; Pou, Rudy (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2024)
Background: The World Health Organization (WHO) estimates that more than 10 million people are sick with tuberculosis and 1.3 million people die from tuberculosis every year. It was recorded that only 59% were reported and the rest were not detected with bacteriological confirmation and were not reported. The coverage of TB patient discovery at the Pasar Minggu District Health Center was 14.35% (101 people out of 704 targets). TB case finding (active case finding) is one of the main strategies and is the first step in TB Control Program (P2TB) activities. Objective: to determine the characteristics, experience (length of work and training), knowledge of TB cadres and analyze the relationship between characteristics and experience and cadre knowledge. Method: quantitative research design with analytical observation, cross-sectional. Implementation in the Asoka Child-Friendly Integrated Public Space (RPTRA) in the Pasar Minggu District area, with implementation time from December 2022 to January 2023. Results: the majority of TB cadres are in the age group > 45 - 60 years (pre-elderly). Cadres with a low level of education are 72%. There is a significant relationship between training and cadre knowledge (p-value = .006). Conclusion: Many TB cadres have no experience because they have worked for less than 5 years. Of all the cadres, there are still many who have not participated in training about TB and the knowledge of TB cadres is relatively low.